KNOWLEDGE MANAGEMENT STRATEGIES FOR VISUALLY IMPAIRED STUDENTS STUDYING IN THE SCHOOLS OF PUNJAB - Samina Ashraf; Amjad Ali Abbasi; Sayyeda Rabia Basri; Saira Hanif (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Knowledge management has appeared as a new discipline. This study was designed to explore the knowledge management strategies in the blind and low-vision students studying in the special education institutions of Punjab. The descriptive research design was used to conduct the study. A structured questionnaire was used as an instrument of the study. The population of the study comprised of students with visual impairment studying in the special education institutes in Punjab province at 6 to 10 grades level, in nine districts one district from all nine divisions ( Blind = 88, Low vision=62). According to the study's findings, blind and low-vision students choose and employ a variety of knowledge management strategies. There is no substantial variation in the knowledge management strategies of blind students based on their location or gender. Availability and use of the latest digital tools to facilitate knowledge management skills of the visually impaired, provision of the latest technology and provision of qualified teachers are major recommendations of this study.